Speaking Strategies in Cross Cultural Adaptation: Gorontalo Students’ Perception in Immersion Context of Kampung Inggris Kediri - Samad, Pratiwi; Dollah, Syarifuddin (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to investigate how English as a Foreign Language (EFL) learners in Gorontalo adapt their speaking skills in a cross-cultural learning context, focusing on the strategies used and challenges faced during classroom interactions. This research uses a qualitative approach based on a strategic competence framework, in which data is collected through in-depth interviews with EFL students to explore how they negotiate linguistic, interactional, and cultural demands in communication. The results show that students predominantly utilise metacognitive, cognitive, and socio-affective strategies to manage speaking tasks and control their performance, particularly when interacting with peers from diverse linguistic backgrounds. However, despite the application of these strategies, learners still face significant challenges, such as limited vocabulary in situations that require fluency, difficulty understanding accent differences, and anxiety in multicultural interactions. These challenges result in hesitation in spontaneous communication and a tendency to avoid requesting clarification. These findings confirm that cross-cultural speaking adaptation depends not only on linguistic ability, but also on learners' affective readiness and sociocultural competence.